In Search of the Ultimate Model - Felton, Melvin (Journal of NeuroPhilosophy, 2023)
In recent years, researchers from a variety of scientific disciplines have begun to notice surprising similarity between the network and topological features of the human brain, or brain-like systems in general, and the picture of the universe emerging out of theoretical physics. In this paper, I discuss some of these recent developments and suggest ways to further investigate structural and dynamical similarities between the human brain and universe. I discuss the impact that a close correspondence between these two systems would have on research in the fields of neuroscience and theoretical physics, and I discuss what type of fundamental underlying processes could have given rise to such a relationship between the brain and universe. Given the high demand in fields like theoretical physics for a system capable of modeling the universe, I suggest a systematic comparison of the ideas emerging out of physics concerning the fundamental nature of the universe, and the ideas emerging out of neuroscience concerning the fundamental nature of the brain and mind.